2020
DOI: 10.1186/s13104-020-05148-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned through piloting a community-based SMS referral system for common mental health disorders used by female community health volunteers in rural Nepal

Abstract: Objective: The Community Informant Detection Tool (CIDT) is a paper-based proactive case detection strategy with evidence for improving help-seeking behavior for mental healthcare. Key implementation barriers for the paperbased CIDT include delayed reporting of cases and lack of active follow up. We used mobile phones and structured text messages to improve timeliness of case reporting, encouraging follow up, and case record keeping. 36 female community health volunteers piloted this mobile phone CIDT (mCIDT) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Digital illiteracy is another barrier that impairs successful implementation of mHealth innovation in Africa, this problem has also been found in implementations in other LMICs ( 27 , 87 ). These challenges are more evident in the rural than urban regions.…”
Section: Discussionmentioning
confidence: 95%
“…Digital illiteracy is another barrier that impairs successful implementation of mHealth innovation in Africa, this problem has also been found in implementations in other LMICs ( 27 , 87 ). These challenges are more evident in the rural than urban regions.…”
Section: Discussionmentioning
confidence: 95%
“…A pilot programme in rural Nepal which tested the feasibility of using mobile phones for collecting health surveillance data reported that community health workers can collect health surveillance data accurately using mobile technology if they are trained adequately [ 31 ]. There have also been studies in Nepal that demonstrated limited uptake of mental illness detection strategies among community health volunteers [ 34 ]. However, the current study differs by focusing on primary care workers and using the app as a decision aid tool, rather than simply documentation and communication.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have assessed the feasibility and effectiveness of the application of mobile technology in health care delivery within the country. These studies have attempted to test if mobile devices can support maternal and new born child healthcare, particularly for patient data collection to send reminders for follow-up and assess signs and symptoms of illness [ 30 ]; gather health surveillance data from rural areas [ 31 ]; SMS reporting of neonatal health information and malaria surveillance [ 32 ]; support health workers in the rural district hospitals, including provision of remote specialists services [ 33 ]; aiding community health volunteers to engage persons with mental illness in treatment initiation at primary care facilities [ 34 ]; and remote supervision for mental health services [ 35 ]. None of these studies has attempted to assess the feasibility of an app-based decision aid for mental health diagnoses in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…The referral system has been widely implemented online to improve efficiency and ease of administration. Bhardwaj et al (2020), in their research on the implementation of SMS-based referral systems in mental health facilities, aim to reduce the gap between mental health facilities and mental health workers in hospitals and conduct online documentation or administration. Other research shows online-based referral systems using platforms, applications, and websites.…”
Section: Implementation Of Referral System In Program Sopmentioning
confidence: 99%